Analisis Kriminologi Kejahatan Pencabulan Sesama Jenis (Homoseksual) yang Dilakukan Oknum Pendamping Paskibraka terhadap Anak: (Studi Kasus di Kepolisian Resor Sikka) - Elisabeth Puji Sri Rejeki; Rudepel Petrus Leo; Rosalind Angel Fanggi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Obscenity is often defined in the Criminal Code, which is a criminal act that contradicts and violates a person's decency and moral norms, all of which are in the environment of sexual lust. This crime of obscenity can deviate further where this crime of obscenity is committed by the perpetrator and the victim is someone of the same sex in this case the perpetrator is a man and the victim is a man as well or can be called (homosexual). The research method used is empirical juridical research. The results of the study show that the occurrence of same-sex abuse crimes is influenced by several factors, namely sexual orientation factors, psychological factors and science and technology abuse factors and child abuse crimes carried out with law enforcement efforts for crimes in pre-emptive efforts, preventive efforts and repressive efforts. The suggestions submitted include: The role of the family, especially parents, should be further improved in shaping a person's personality must be done from the moment a person is in the process of forming a personality and In order to be able to suppress and break the chain of the crime of same-sex molestation (homosexual) against children, it is necessary to improve the provisions in the Criminal Code and Law No. 23 of 2002 in conjunction with Law No. 35 of 2014 concerning Child Protection, namely by amending criminal penalties For perpetrators of sexual violence against children, it becomes life or the death penalty.